61.5k views
4 votes
combining functionsConsider the following functions. f(x) = x^2 + 8 and g(x) = x + 6 Find (fg)(-2)(fg)(-2)=

User ToddT
by
5.3k points

1 Answer

2 votes

hello


\begin{gathered} f(x)=x^2+8 \\ g(x)=x+6 \end{gathered}
\begin{gathered} (f\mathrm{}g)(-2)= \\ we\text{ find f.g first and the multiply the answer by -2} \end{gathered}
\begin{gathered} f\mathrm{}g=(x^2+8)(x+6) \\ f\mathrm{}g=x^3+6x^2+8x+48 \end{gathered}

now we can find f.g(-2) by simply multiplying -2 all through f.g


\begin{gathered} (f\mathrm{}g)(-2)=(x^3+6x^2+8x+48)(-2) \\ (f\mathrm{}g)(-2)=-2x^3-12x^2-16x-96 \end{gathered}

User Vinay Gaba
by
5.9k points